2009
DOI: 10.1097/ico.0b013e318183a396
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival Impression Cytology, Ocular Surface, and Tear-Film Changes in Patients Treated With Systemic Isotretinoin

Abstract: Conjunctival epithelial cells, tear basal secretion, and tear quality are markedly affected in patients during systemic treatment with isotretinoin (0.8 mg/kg). Ocular adverse effects of isotretinoin are generally not serious and are reversible after discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 27 publications
5
29
0
4
Order By: Relevance
“…RA causes keratinization and thickening of the meibomian gland ducts (Lambert and Smith 1989), degeneration and necrosis of the acinar cells (Kremer and others 1994), fibrosis of the periacinar tissue, and reduced lipid content in meibomian gland (Lambert and Smith 1989). Further, isotretinoin exposure is associated with tear film instability and hyperosmolarity, dry eye symptoms and blepharitis (Bozkurt and others 2002; Fraunfelder 2004; Karalezli and others 2009; Santodomingo-Rubido and others 2008). In effect, RA promotes MGD and evaporative dry eye disease (Knop and others 2011).…”
Section: Anti-aging Treatment- Potential Influence On Mgd and Dry Eyementioning
confidence: 99%
“…RA causes keratinization and thickening of the meibomian gland ducts (Lambert and Smith 1989), degeneration and necrosis of the acinar cells (Kremer and others 1994), fibrosis of the periacinar tissue, and reduced lipid content in meibomian gland (Lambert and Smith 1989). Further, isotretinoin exposure is associated with tear film instability and hyperosmolarity, dry eye symptoms and blepharitis (Bozkurt and others 2002; Fraunfelder 2004; Karalezli and others 2009; Santodomingo-Rubido and others 2008). In effect, RA promotes MGD and evaporative dry eye disease (Knop and others 2011).…”
Section: Anti-aging Treatment- Potential Influence On Mgd and Dry Eyementioning
confidence: 99%
“…Karalezli et al (14) observed blepharitis in 36 % of patients 1 month after the cessation of treatment. It was accompanied by dysfunction of meibomian glands, hyperemia and vascularization of the lid margin.…”
Section: Adverse Ocular Effectsmentioning
confidence: 99%
“…In our opinion, this might be assumed as an indirect effect of retinoid acid whereas direct action should also be taken into consideration. It is caused by the presence of the drug and its metabolites in the tear film (14), which may directly provoke its instability, hence dryness and irritation. We emphasize that both of these mechanisms are predis- .…”
Section: Adverse Ocular Effectsmentioning
confidence: 99%
See 2 more Smart Citations